The REBECGA Brazilian Registry of Pregnancy and Heart Disease: Rationale and Design - Avila,Walkiria Samuel (2021)
Abstract Background: Maternal mortality rates in Brazil remain above the goals established by the United Nations Sustainable Development Goals. Heart disease is estimated to affect 4% of all pregnancies and remains by itself the main indirect obstetric cause of maternal death. In the last decades, a significant improvement in the prognosis of heart diseases has made pregnancy possible in women with heart disease and provided better maternal and fetal outcomes. Objective: To establish a multicenter Brazilian Registry of pregnant women with heart disease; to study the causes of immediate and late maternal mortality; and to assess the prevalence of heart disease in the country’s macro-regions. Method: This is an observational study, with retrospective and prospective stages, of the clinical and obstetric progression of pregnant women with heart disease. These women consecutively received care during pregnancy and will be followed up for up to a year after delivery at public and private hospitals with infrastructure for the execution of this project, a principal investigator, and approval by Ethics and Research Committees. Results: Our results will be presented after data collection and statistical analysis, aiming to demonstrate immediate and late maternal mortality rates, as well as the prevalence of heart disease in the country and its cardiovascular and obstetric complications during pregnancy. Conclusion: REBECGA will be the Brazilian Registry of heart disease and pregnancy and it will contribute to planning preventive measures, raising financial resources for the improvement of high-risk prenatal care, and reducing immediate and late maternal mortality due to heart disease.